CATCH RATE AND CATCH COMPOSITION OF FISH TRAWL BASED IN SIBOLGA, NORTH SUMATERA - Agustinus Anung Widodo; Mahiswara Mahiswara (Indonesian Fisheries Research Journal, 2011)
To obtain data and information of fish trawl fishery performance operated in the Indian Ocean, a research was carried out through observation on board by observers as well as port sampling inSibolga Fishing Port by enumerators in September 2007, with the aimed to study the performance fish trawl fishery. These include fleet structure, trawl net design and construction, catch, fishing trip, fishing ground, and fishing operation. Results of research showed that there were 71 registered fish trawlers in Sibolga Fishing Port and only 25 boats active due to increasing of fuel price. The fleet structure of fish trawler consist of boat with size 31-114 GT which can be classified into 3 categories i.e. small(<60 GT), medium (60-150 GT), and large fish trawler (>150 GT). Design and construction of fish trawl net indicated that fish trawl net operates in the Indian Ocean was high opening trawl with head and ground rope of 27.8-41.5 m and 29,7-45.8 m, respectively. Fishing trip generally 10-12 days with effective days 7-9 days per trip and the number of net setting was 5-6 times each day. The fishing grounds of fish trawl based in Sibolga were the coastal waters area with maximum depth of 91 m. At least 40 species of fishes and shrimps identified during research and dominant fish species was ponyfish (Leiognathus spp.) threadfin bream (Nemipterus spp.), tall fin goatfish (Upeneus spp.), seacatfish (Arius sp.) as well as yellow striped goatfish (Upeneus vitattus). The average of catch of fish trawler fleet in the year of 2007 was 249.3 kg/haul and that number seems smaller than average of catch/haul previous years. This situation indicates that decreasing of catch per haul of fish trawlers based in Sibolga continues occurring and in other hand price of fuel raises significantly so that big fish trawlers size 150 GT with engine power more than 600 HP are not able to continue their fishing operation.